A study of Serum Steroid Hormones Concentrations Of Pregnant Cows - H., AL-Anbaky K. I. (The Iraqi Journal of Veterinary Medicine, 2009)
The objective of present work is to estimated peripheral blood serum concentrations of pregnancyhormones, oestradiol , progesterone and testosterone , in cows . For this purpose 24 Frezain- Holsteincows at different stages of pregnancy the blood samples were taken from jugular veins. The serumwere separated and frozen at – 20 c until analysis. The serum hormones were measured by a specificELISA technique (ELISA Linear Multi Reader). The data were represented Mean + S.D. Progesteronewas high during pregnancy reaching a maximum of 91.94 + 26.09 ng/ml during last thirds (6-8months) of pregnancy , but was below 9.12 + 2.41 ng/ml for several months during the pregnancy.Oestradiol levels varied from 9.0+ 2.89 pg/ml in the first thirds of pregnancy to 282.6 + 48 .514 pg/mlduring the last month of gestation. While testosterone hormone level was low 0.32 + 0.12 ng /mlduring pregnancy. The result indicated that the major sources of hormones appeared to be the 0vary(corpus luteum ) and the uterus (placenta). The ovarian contribution was greater during the first – thirdsof pregnancy than later, whereas that made by the placenta was higher during the last thirds ofpregnancy